Left Stellate Ganglion Block for Continuous Ventricular Arrhythmias during Percutaneous Left Ventricular Assist Device Support - Loyalka, Pranav (Texas Heart Institute, 2011)
A 58-year-old man presented with chest pain and tightness and was diagnosed with a Q-wave anterior myocardial infarction. He then developed pulseless ventricular arrhythmias, which were treated with repeated direct-current shocks and intravenous amiodarone. He underwent emergency cardiac catheterization: stents were deployed in the left anterior descending coronary artery and right coronary artery, and an intra-aortic balloon pump was inserted. Severe refractory cardiogenic shock and incessant ventricular arrhythmias compelled us to place a TandemHeart percutaneous left ventricular assist device 4 hours later. The patient's hemodynamic status stabilized, but the arrhythmias persisted for 36 hours. Multiple doses of intravenous amiodarone and lidocaine and multiple external direct-current shocks were all tried, but these measures failed to terminate the life-threatening ventricular arrhythmias. We performed a pharmacologic block of the left stellate ganglion, and this resulted in a return to sinus rhythm after 1 direct-current shock. To our knowledge, this is the 1st patient with refractory ventricular arrhythmias to have been treated with TandemHeart support and left stellate ganglion block.